Factors influencing professional values among Indonesian undergraduate nursing students - Nelwati, -; Abdullah, Khatijah Lim; Chong, Mei Chan (Elsevier, 2019)
Background: Undergraduate nursing students are required to acquire professional values during professional nurse education to provide safe and high quality patient care. However, there was no documentation in professional values among Indonesian undergraduate nursing students and the factors influencing its development. Purpose: The purpose of this study was to determine professional values among Indonesian undergraduate nursing students and examine the relationship between students’ demographic factors and professional values. Design: A cross-sectional study using convenience sampling was applied to recruit 391 Indonesian undergraduate nursing students. The 26 items of Nurses Professional Values Scale Revision (NPVS-R) with five dimensions was employed to collect data. Descriptive and inferential statistics, independent samples t-test were applied to analyse and interpret data. Results: The result showed that the total score of nurse professional values was high (95.80 ± 12.93). The most important professional value dimension was caring, while activism was the least important values. The NPVS-R total score had a significant association with length of professional clinical practice of the students (p < .05). Conclusion: Nurse educators need to consider the integration of professional values when developing nursing curriculum, in order to ensure that the students develop their own understanding of these values and their importance in practice. © 2019 Elsevier Ltd